Just got bored, but here is poll. if this is too much pls pm me or shadow

a = b

a^2 = ab

a^2-b^2 = ab-b^2

(a-b)(a+b) = b(a-b)

a+b = b

a = 2a!!!

1 = 2

Is this correct??!!

- Yesâ€¦Idk why it works
- NO!!(Add reason in reply)

Just got bored, but here is poll. if this is too much pls pm me or shadow

a = b

a^2 = ab

a^2-b^2 = ab-b^2

(a-b)(a+b) = b(a-b)

a+b = b

a = 2a!!!

1 = 2

Is this correct??!!

- Yesâ€¦Idk why it works
- NO!!(Add reason in reply)

0
voters

2 Likes

Iâ€™m confuzzled where did you get the 1 and 2 from? Couldnâ€™t it be 2 and 4 or 6 and 12 etc?

1 Like

No, in this case, a and b would be the same.

1 Like

a^2 - b^2 = (a-b)*(a+b)

1 Like

(a-b)^3 = a^3 - 3a^2b + 3ab^2 - b^3

1 Like

ye, but just a example

1 Like

it think cuz u can directly delete the facter, so it doesnâ€™t work. i found it out long time ago, forgot tho

The issue is in these two lines. Youâ€™ve stated that a = b, so a - b would be equal to 0.

Dividing both sides by (a-b) would mean dividing by 0, which is not gud.

im confused, Me dumb

Ye, that was what i thought, but then, if a-b = 0

doesnâ€™t any a and b add up into b?

idk this doesnt work

1 Like

Any steps after dividing by 0 just isnâ€™t valid.

ye ik lol

lool just look at the poll most dont know why lmao

1 Like

wdym by tht

no like it equals zero, so it doesnâ€™t work

This topic was automatically closed after 7 days. New replies are no longer allowed.